The effect of Service Quality, Pricing, and Costumer Satisfaction on Costumer Loyalty Gojek Transportastion at 3rd Hamlet Paseban District, Central Jakarta - Ruwaida, Ruwaida; Sihombing, Furwati; Kurniawati, Sri; Sulaiman, Anwar (Journal of Industrial Engineering & Management Research, 2023)
The use of online transportation in Indonesia is increasing every year, one type of online transportation in Indonesia is Gojek. This study aims to determine the effect of service quality, pricing, and customer satisfaction on customer loyalty in gojek transportation. The population in this study at 03rd hamlet paseban District, totaling 140 people who had used gojek transportation services with at least one use. The nmber of samples used in this study were 104 people. This study used a purposive sampling metod. In managing data, researchers use structural equation modeling (SEM) and SmartPLS Software. the results obtained from this study indicate that service quality has a positive and significant effect on customer loyalty for Gojek transportation. Pricing has positive effect on customer loyalty for Gojek transportation. The independent variable contribution to the dependent variable is 73%. The remaining 27% is influenced by other variables not examined in this study, such as promotion and brand image variables.